2018
DOI: 10.1177/0038040718801760
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in Reading and Math Skills Forms Mainly before Kindergarten: A Replication, and Partial Correction, of “Are Schools the Great Equalizer?”

Abstract: When do children become unequal in reading and math skills? Some research claims that inequality grows mainly before school begins. Some research claims that schools cause inequality to grow. And some research-including the 2004 study ''Are Schools the Great Equalizer?''-claims that inequality grows mainly during summer vacations. Unfortunately, the test scores used in the Great Equalizer study suffered from a measurement artifact that exaggerated estimates of inequality growth. In addition, the Great Equalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
206
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(233 citation statements)
references
References 57 publications
25
206
0
2
Order By: Relevance
“…This article challenges older findings from seasonal comparisons studies that found equalizing effects of schooling in the US and other European countries and accord with more recent accounts that questioned those earlier findings based on methodological shortcomings (von Hippel & Hamrock, 2019b;von Hippel et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This article challenges older findings from seasonal comparisons studies that found equalizing effects of schooling in the US and other European countries and accord with more recent accounts that questioned those earlier findings based on methodological shortcomings (von Hippel & Hamrock, 2019b;von Hippel et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
“…Studies employing the seasonal comparison design (hereafter: SCD) have dominated sociological research on schooling effects for the last 40 years (Alexander, Entwisle, & Olson, 2007;Downey et al, 2004;Entwisle & Alexander, 1992;Hayes & Grether, 1983). Only recently, proponents of the SCD themselves have criticized it for being prone to various statistical artifactssuch as scaling of tests and comparability of test formsthat might have led to an overestimation of schooling's equalizing role (von Hippel & Hamrock, 2019a;von Hippel, Workman, & Downey, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…() found, many public school kindergarten teachers in 2010 (compared to 1998) believe that “academic instruction should begin prior to kindergarten entry.” Furthermore, these changes “were more pronounced among schools serving high percentages of low‐income and non‐White children, particularly with respect to teacher expectations and didactic instruction” (p. 14). Furthermore, recent evidence suggests that the income‐based achievement gap in reading does not get smaller across the elementary years (von Hippel, Workman, & Downey, ). Thus, we must consider how to “language‐ize” children's homes, day cares, and schools to meet this challenge, especially as low‐income children experience the brunt of these changes (Masek et al., in press).…”
Section: Language Is Key To Children's School Achievementmentioning
confidence: 99%
“…Education is a key predictor of life outcomes (Hout & DiPrete, 2006), including physical health (Schütte, Chastang, Parent Thirion, Vermeylen, & Niedhammer, 2013), mental health (von dem Knesebeck, Pattyn, & Bracke, 2011), subjective well-being (Blanchflower & Oswald, 2000), life expectancy (Meara, Richards, & Cutler, 2008), trust (Easterbrook, Kuppens, & Manstead, 2015), and income (Britton, Dearden, Erve, & Waltmann, 2020;Card, 1999). Those with higher qualifications are also more engaged in politics and are more likely to vote, giving them a louder political voice (Bynner & Ashford, 1994;Helliwell & Putnam, 2007;Persson, 2013;Stubager, 2008).…”
mentioning
confidence: 99%